High prevalence of congenital deafness on Reunion Island is due to a founder variant of LHFPL5. Issue 1 (4th November 2018) - Lerat, Justine; Bonnet, Crystel; Cartault, François; Loundon, Natalie; Jacquemont, Marie‐Line; Darcel, Françoise; Rouillon, Isabelle; Mezouaghi, Kheira; Guichet, Agnes; Litzler, Julie; Gesny, Roselyne; Gherbi, Souad; et al.
Abstract : Reunion Island is a French oversea department in the Indian Ocean with 1.6/1000, an estimated prevalence of deafness that is almost double as compared to the mainland France. Twelve children having isolated bilateral prelingual profound deafness along with motor delay attributed to vestibular areflexia were enrolled. Their mean walking age was 19 months. Electroretinography and temporal bone CT‐scans were normal in all cases. A novel homozygous frameshift lipoma HMGIC fusion partner‐like 5 ( LHFPL5 ) variant c.185delT p.(Phe62Serfs*23) was identified using whole‐exome sequencing. It was found in seven families. Four patients from two different families from both Reunion Island and mainland France, were compound heterozygous: c.185delT p.(Phe62Serfs*23) and c.472C > T p.(Arg158Trp). The phenotype observed in our patients completely mimics the hurry‐scurry (hscy) murine Tmhs knock‐out model. The recurrent occurrence of same LHFPL5 variant in Reunion Island is attributed to common ancestor couple born in 1693. Abstract : A highest prevalence of congenital deafness is noticed among the Reunionese population with a similar phenotype: isolated bilateral profound congenital deafness with motor delay because of bilateral vestibular areflexia without cochleo‐vestibular malformation and Retinitis Pigmentosa. A novel homozygous frameshift lipoma HMGIC fusion partner‐like 5 (LHFPL5) variant c.185delT p.(Phe62Serfs*23) was identified using WES. A founder effect was determined thanks to the founder haplotype and the common ancestor couple, born in 1693.